Hydromorphological method and GIS tools with a web application to assess a semi-natural urbanised river - Bedla, Dawid; Halecki, Wiktor; Król, Karol (Journal of Environmental Engineering and Landscape Management, 2021)
River valleys are an essential element of urban space, and play an important role in the functioning of the natural environment and the recreation of city dwellers. Moreover, blue-green infrastructure facilitates healthy urban living. New technologies can contribute significantly to dissemination of messages of environmental protection. We discuss adaptation of the RHS method for presenting interactive data for river channels. Our assessment was focused on three parameters: habitat area, structure and conservation. The main parameters were described using selected indicators linked to natural and anthropogenic factors. The habitat modification score showed that the physical state of the Drwinka River was obviously modified, and the habitat quality assessment rated the stream as hydromorphological class III. The web application showed that the proposed method is suitable for creating realistic visual effects, and indicates greening areas against degraded areas.